Analysis of the Impact of ESG Integration and Risk Governance on Cost of Capital and Company Value in Manufacturing Issuers in West Java - Karim, Abdul (Westscience Press, 2025)
This study analyzes the impact of Environmental, Social, and Governance (ESG) integration and risk management on capital costs and company value among manufacturing issuers in West Java. Using a quantitative approach with 110 samples, data were collected through a Likert scale (1–5) questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results show that both ESG integration and risk management have a significant positive influence on reducing capital costs and enhancing company value. Furthermore, the analysis reveals an indirect effect, where capital costs mediate the relationship between ESG integration, risk management, and company value. These findings highlight the strategic importance of sustainability and risk control in improving financial outcomes and ensuring long-term corporate growth. The study contributes to the literature by providing empirical evidence from the Indonesian manufacturing sector, while offering practical implications for managers, investors, and policymakers in promoting responsible and resilient business practices.